Strengthening the Character of Patriotism Through the Narantika Rarangganis Dance at a Senior High School in Cimahi - Jajang Hendar Hendrawan; Lili Halimah; Kokom Kokom (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the implementation of Narantika Rarangganis Dance, instilling patriotism's value. This research uses a case study method with a qualitative approach. The participants that were involved in this study were three teachers from a state senior high school in Cimahi Regency. These participants were senior teachers aged above 50 years old. The results of the study show that (1) the implementation plan of the Cultural Arts Learning for dance branch refers to the curriculum in accordance with basic competencies, planting the character of patriotism is formed from the values of local wisdom in the form of surti, harti, evidence and devotion which is realized by restoring character education as an alignment between knowledge, skills and attitudes. (2) The Cultural Arts Learning Process based on local wisdom by demonstrating the Narantika Rarangganis dance as a West Java regional dance that continuously has a peace-loving character, defends the country, kinship or friendship and upholds the value of local wisdom by maintaining and developing it. (3) Efforts to instill the character of patriotism through Cultural Arts Learning by carrying out cultural performances, language month, carrying out character building, getting to know regional culture, implementing school superior programs, including preserving regional culture, (4) How to preserve local wisdom of Narantika Rarangganis Dance by participating in performing dances at every cultural performance activity both at school and outside of school, participating in the national student art competition festival, holding education and training targeting junior high, high school students and teachers. Recommendations are addressed to school principals, teachers, and future researchers.